Regional cerebral perfusion alterations in patients with mild cognitive impairment and Alzheimer disease using dynamic susceptibility contrast MRI - Hauser, Thomas; Schönknecht, Peter; Thomann, Philipp; Gerigk, Lars; Schröder, Johannes; Henze, Romy; Radbruch, Alexander; Essig, Marco (Academic radiology, 2013)
Rationale and Objectives - The purpose of this study was to assess regional cerebral perfusion distribution in patients with Alzheimer disease (AD) or mild cognitive impairment (MCI) using dynamic susceptibility contrast magnetic resonance imaging. - Materials and Methods - Regional changes of perfusion were evaluated in 34 patients with AD, 51 patients with MCI, and 23 healthy controls (HCs). Using region of interest analyses, regional cerebral blood flow (CBF), cerebral blood volume, and mean transit time were measured bilaterally in the hippocampus; the temporal, temporoparietal, frontal, and sensomotoric cortices; the anterior and posterior cingulate gyri; the lentiform nucleus; and the cerebellum. - Results - A significant reduction of CBF in patients with AD compared to HCs was shown in the frontal and temporoparietal cortices bilaterally, the lentiform nuclei bilaterally, the left posterior cingulate gyrus, and the cerebellum. Compared with patients with MCI, patients with AD presented a reduction of CBF in the frontal cortices bilaterally, the left temporoparietal cortex, and the left anterior and posterior cingulate gyrus. In both hippocampi and the posterior cingulate gyrus, a trend to a slight increase of CBF in patients with MCI was noticed with a decrease in patients with AD. - Conclusions - Using dynamic susceptibility contrast magnetic resonance imaging, pathologic alterations of regional brain perfusion can be demonstrated in patients with AD compared to patients with MCI or HCs.